Association Situation and Educational Situation in Elementary School - WIDIANSYAH, Apriyanti (PT. Keberlanjutan Strategis Indonesia, 2023)
Purpose The research aims to find out how the situation of the association in shaping education both in social situations and education in elementary schools.MethodologyThe research methodology used is Descriptive Qualitative Research, intending to obtain an overview of the correlative dimensions of the synergism of social situations and educational situations in elementary schools, with the hope of developing substantive thinking as a whole (not dichotomous and partial). The data collection techniques used include: First, Observation, ; Second, interviews; Third, literature; Fourth, Documentation.FindingsWhen it comes to social situations and educational situations, educators, including teachers as educators at school, need to keep in mind carefully so that they can place themselves in the correct position in every situation that may be encountered in carrying out their duties as a teacher/educator. A teacher must know when he is just hanging out with his students and when he is educating or being an educator. In order not to act wrongly because, for ordinary people, the two situations are the same, and call them by the same name.ImplicationNo two children are identical in this world. In social situations, children get the opportunity to express what they live. Children can freely and spontaneously express their thoughts, feelings, and desires. Children can develop their personality with the opportunity to act and behave as he wants. On the one hand, children do feel dependent on adults, but on the other hand, children want to gain freedom or independence. This desire can be obtained by children in the association.